An Ethical investigation of State and the Management of Internally Displaced Persons in Nigeria - Ifeanyichukwu Micheal Abada; Nneka Ifeoma Okafor (Department of Government Studies Universitas Muhammadiyah Makassar, 2017)
The spontaneous displacement and wandering of men had always been propelled by the forces of nature and other anthropogenic activities. Man, as a rational being had remained strategical for their survival. The upsurge in the activities of Boko Haram in Nigeria, north east occasioned by their clientele interests had necessitated decisions by men to forcefully relocate their places of abode. However, the purpose of the study is to ethically investigate whether the ineffective curtailment of the activities of Boko Haram had implicated the increasing vulnerabilities of internally displaced persons. The study utilized qualitative method in generating its data, while the theoretical framework was adequately anchored on the Marxist theory of the post-colonial state. The findings of the study had significantly revealed that the ineffective management of Boko Haram menace by the state had implicated the rising vulnerabilities of internally displaced persons. However, the study recommends among other things, the integration of relevant commission and prosecution of personality-cults engage in sabotaging the efforts of the state.